Semantic Web science and real-world applications - Lytras, Miltiadis D. 1973-; Aljohani, Naif 1983-; Damiani, Ernesto 1960-; Chui, Kwok Tai (IGI Global, 2019)
"This book focuses on information systems discipline and working towards the delivery of the main implications that the semantic web brings to information systems and the information/knowledge society. It discusses the technology of the semantic web in the context of information systems. It establishes knowledge transfer and personal development channels in these areas: academia, industry, and government"--Provided by publisher